Fundamentals of photovoltaic modules and their applications - Tiwari, G. N. (RSC energy series, 2010)
Presently there is no single publication available which covers the topics related to photovoltaic (PV) or photovoltaic thermal (PV/T) technologies, thermal modelling, CO2 mitigation and carbon trading. This book disseminates the current knowledge in the fundamentals of solar energy, photovoltaic (PV) or photovoltaic thermal (PV/T) technologies, energy security and climate change and is aimed at undergraduate and postgraduate students and professionals. The main emphasis of the book is on the design, construction, performance and application of PV and PV/T from the electricity and thermal stan.